Biotechnology and development challenges and opportunities for Asia - Chaturvedi, Sachin; Rao, S. R. (Institute of Southeast Asian Studies, 2004)
Contributed articles presented earlier at the International Conference on Biotechnology and Development: Challenges and Opportunities for Asian Region, February 26-27, 2002 at New Delhi, India organized by RIS.